Biomechanical effects of orthodontic tooth movement on edentulous alveolar bone: a finite element analysis - Wang, Xiaoxu; Xue, Jiaojiao; Wang, Xiaoting; Fan, Mingyue (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study investigates the biomechanical effects of different orthodontic movement patterns on the alveolar bone in the adjacent edentulous region through finite element analysis (FEA) of maxillary central incisor displacement mechanisms.MethodsA three-dimensional FEA model was constructed comprising the maxilla, upper dentition (with exclusion of the right maxillary central incisor), periodontal ligament (PDL), fixed orthodontic appliance bracket, and archwire system. The initial displacement characteristics and stress distribution patterns of the maxillary left central incisor (tooth 21) and the surrounding alveolar bone were quantitatively analyzed using ANSYS software.ResultsUnder an intrusion force approximately four times the lingual reactionary force, the maxillary central incisor underwent pure axial intrusion without labial or lingual tipping. Adjacent tooth movement had minimal mechanical impact on the edentulous alveolar bone (<0.5% strain). The resistance center of the incisor was identified 0.43 times the root length apical to the alveolar ridge crest, necessitating precise force vector alignment to achieve bodily movement without rotational displacement or alveolar bone remodeling. For incisal tipping correction, a horizontal tensile force (F) combined with an archwire-bracket-induced moment (M) allows controlled tipping via modulation of the M/F ratio. However, excessive force risks pathological root resorption and alveolar bone atrophy in edentulous regions.ConclusionBodily movement of the central incisor, when guided through the resistance center, does not significantly remodel the edentulous alveolar bone. Moreover, effective tipping correction requires precise M/F ratio control to optimize movement efficiency while minimizing iatrogenic risks. Deviations from optimal force parameters substantially increase the likelihood of alveolar bone atrophy.